2019
DOI: 10.5324/nordis.v0i26.3280
|View full text |Cite
|
Sign up to set email alerts
|

Practical Notes on the Measurement and Interpretation of Thermally Stimulated Discharge Currents in Biaxially Oriented Polypropylene

Abstract: The measurement and interpretation of high-field thermally stimulated depolarization current (TSDC) of capacitor-grade biaxially oriented polypropylene (BOPP) films are investigated in order to facilitate the derivation of trap parameters. Two main relaxations associable with the glass transition and detrapping of space charge from deep traps are observed, and their dependence on the polarization/depolarization conditions are studied. The complex bipolar nature of the space charge relaxation makes the derivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Rytöluoto et al [131] reported recently on TSDC from Polypropylene capacitors. Trap energies in the range from 0.3 to 1.3 eV were obtained by multi-peaks fitting, with positive or negative contributions to the glow peaks.…”
Section: Thermally Stimulated Currentsmentioning
confidence: 99%
“…Rytöluoto et al [131] reported recently on TSDC from Polypropylene capacitors. Trap energies in the range from 0.3 to 1.3 eV were obtained by multi-peaks fitting, with positive or negative contributions to the glow peaks.…”
Section: Thermally Stimulated Currentsmentioning
confidence: 99%
“…For neat BOPP films, the typically observed TSDC features include 18,86 : (i) a small heteropolar (α-) relaxation peak at −6 °C associable with de-trapping of charge from shallow traps as the polymer passes the glass-transition (cf. Table S1) and (ii) a strong (bipolar) space charge (ρ-) relaxation in high temperature region (~100 °C) which is due to the thermal release of captured charges from deep traps.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…For the silica compounds however, the TSDC spectra above 𝑇 𝑔 became more pronounced and complex, indicating higher presence of shallow (or rather, "inter-level" 87 ) traps with trap depths in the 0.7-0.9 eV range in comparison to neat BOPP. In the high temperature region (~90 °C and above), the unfilled BOPP films exhibited strong TSDC peaks corresponding to charges released from deep traps (in the range of 1.1-1.3 eV), often being anomalous in the sense that the current flow was in the same direction as the polarization current (polarity reversal) which is a result from drifting of thermally de-trapped charge under the internal field caused by the space charge 86 . For the silica-BOPP films however, the (bipolar) TSDC intensity in the deep trap region was greatly reduced, being indicative of modification of the apparent (occupied) deep trap density with nanosilica.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 2 more Smart Citations